Assessing the impact of breastfeeding on oral health and facial development - Corrêa, Suelen Castro Lavareda; Uchôa, Sue Ann Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vania Castro (Seven Editora, 2024)
Breastfeeding emerges as an essential pillar for child health and development, not only as a balanced nutritional source, but as an agent that promotes the affective bond between mother and child. The relevance of this act transcends food barriers, encompassing fundamental benefits for the baby's immune system, strengthening the foundations for their psychological and physical development. Thus, this study proposes a literature review of the influence of breastfeeding on facial growth and development. Breastfeeding has a significant impact on many aspects, from the development of the teeth to the facial structure. In addition, it contributes to the improvement of essential sucking, chewing, swallowing and breathing movements. This positive interaction culminates in a proper bite and sustains a better future quality of life. This establishes a dynamic balance between the facial anatomy and the oral cavity. Thus, the crucial role of dentists in promoting breastfeeding is concluded. In addition to dental practices, these professionals have the potential to guide mothers about the intrinsic importance of breastfeeding, not only as a nutritional factor, but also as an essential determinant for the proper development of the child. This comprehensive approach, both nutritionally and skeletally, converges towards harmonious orofacial growth, positively influencing the child's oral and overall health. DOI: https://doi.org/10.56238/sevened2023.007-031